266 DIETARY PROTEIN INDUCES REMNANT KIDNEY INJURY BY INCREASED INTRINSIC ACID PRODUCTION MEDIATED THROUGH ENDOTHELIN RECEPTORS. Issue 1 (1st January 2007) - Phisitkul, S.; Hacker, C.; Simoni, J.; Tran, R. M.; Wesson, D. E.
Abstract : Purpose: We tested the hypothesis that acid-producing dietary protein induces endothelin-mediated parenchymal injury in the 5/6 nephrectomized rat by increasing intrinsic acid production. Methods: Munich-Wistar rats underwent surgical 5/6 nephrectomy (Nx) and were studied 12 weeks after eating diets with either acid-producing protein (casein) or non-acid-producing protein (soy). Intrinsic acid production in the casein group was reduced by added Ca ++ citrate with Ca ++ phosphate as a control. Intrinsic acid production in the soy group was increased by added (NH4 )2 SO4 with Na2 SO4 as a control. Both casein-eating Nx and soy + (NH4 )2 SO4 -eating Nx received either the oral endothelin A/B receptor antagonist bosentan or the oral endothelin A antagonist darunsentan. Distal nephron Net HCO3 reabsorption (Net JHCO3 ) was measured at 4 weeks by in vivo microperfusion. Urine endothelin 1 excretion (UET-1 V), urine albumin excretion (Ualb V), kidney glomerulosclerosis (GS), and tubulointerstitial injury (TII) were measured at 12 weeks. Results: (1) Casein-eating Nx versus soy-eating Nx had higher UET-1 V (315 ± 52 vs 78 ± 13 fmol/d, p < .05), higher Ualb V (180 ± 22 vs 74 ± 10 mg/d, p < .05), greater GS (2.8 ± 0.3 vs 1.5 ± 0.2 units, p < .05), and greater TII (3.5 ± 0.3 vs 1.9 ± 0.2 units, p < .05). (2) Casein-eating Nx additionally eating Ca ++ citrate versus Ca ++ phosphate had lower UET-1 V (89 ± 22 vs 341 ± 56 fmol/d, p < .05), lower Ualb V (105 ± 11 vs 177 ± 20 mg/d, p < .05), less GS (1.7 ± 0.1 vs 2.7 ± 0.2 units, p < .05), and less TII (2.2 ± 0.2 vs 3.3 ± 0.2 units, p < .05). (3) Soy-eating Nx additionally eating (NH4 )2 SO4 versus Na2 SO4 had higher UET-1 V (350 ± 40 vs 211 ± 26 fmol/d, p < .05), higher Ualb V (145 ± 16 vs 86 ± 10 mg/d, p < .05), greater GS (2.4 ± 0.2 vs 1.6 ± 0.2 units, p < .05), and greater TII (2.8 ± 0.2 vs 2.0 ± 0.2 units, p < .05). (4) The endothelin A/B but not endothelin A antagonist reduced Net JHCO3 in acid-ingesting groups. By contrast, the endothelin A but not endothelin A/B antagonist reduced Ualb V and TII in acid-ingesting groups. Conclusions: Acid-producing dietary protein induces endothelin B-mediated increased acidification and endothelin A-mediated TII in the 5/6 nephrectomized rat through increased intrinsic acid production.